How well have we been educationg our patients? Patients’ perception of control and knowledge, attitude and practice of their diabetes mellitus management - Shahar, Mohammad Arif; Anwardeen, Azmad Kareem; Jalunis, Mohamad Mustakim; Mohammad Isa, Muhammad Syafiq; Omar, Ahmad Marzuki; Kamaruddin, Nor Azmi (2013)
Background: There is discordance between knowledge, attitude and practice (KAP) and true diabetic control in many previous study. The current study attempts to analyze patients’ perception of their diabetic control in association with true diabetic control in terms of glycated hemoglobin (HBA1C). Methods: A cross-sectional study was performed involving 120 diabetic patients. Sociodemographic data and most recent biochemical investigation results were tabulated and they were interviewed using KAP questionnaire. The association between patient perception, actual control (HbA1C) and KAP scores were analyzed. Results: Sixty-two percent believe that their diabetes is well controlled with median HbA1C of 8.0 (6.9 - 9.2) % [64 (52 - 77) mmol/mol], which is significantly lower compared to those who perceive their diabetes is partially and uncontrolled [10.25 (8.43 - 12.00) and 10.25 (8.48 - 13.50)%] [89 (69 - 108) and 89 (69 - 124) mmol/mol], p-value = 0.026. Patients who perceive controlled diabetes have lower median postprandial glucose level compared to those with partially and uncontrolled although higher than recommended target, p-value = 0.010 (Table 1). Overall KAP score and each of their domains were significantly higher in those with HbA1C 6.5-8.0% (48 - 64 mmol/mol) compared to those outside the recommended target (Table 2). No association was found between perception of diabetic control and KAP scores (Table 3). Conclusion: Sixty-two percent of patients felt that their diabetes is well controlled despite having median HbA1c of 8.0%. KAP score on the other hand did not correlate with patients perception of how well their diabetes mellitus control was.